Biodeterioration of pre-treated polypropylene by Aspergillus terreus and Engyodontium album - Amira Farzana Samat; Dee Carter; Ali Abbas (npj Materials Degradation, 2023)
Abstract Polypropylene (PP) has raised severe environmental issues concerning its non-degradability, with a current recycling rate of only 1%. This current study utilises Aspergillus terreus ATCC 20542 and Engyodontium album BRIP 61534a to break down PP while focusing on pre-treatment. Polypropylene granule (GPP), film (FPP) and metallised film (MFPP) are pre-treated by either UV, heat, or Fenton’s reagent. UV and heat-treated MFPP by A. terreus exhibits notable weight loss percentage (25.29% and 22.13%, respectively). Biomass production, reduction rate, Fourier transform infrared (FTIR), and scanning electron microscopy (SEM) analyses further validate the degradation rate. A. terreus incubated with UV-treated MFPP produced a relatively high biomass yield of 1.07 mg/ml. Reduction in carbonyl index and surface morphological changes reveal consistent biodeterioration evidence. This investigation demonstrates that A. terreus and E. album can grow on, change, and utilise PP as a carbon source with pre-treatments’ aid, promoting the biological pathways for plastic waste treatment.